Thirteen-level inverter for photovoltaic applications - Lasanthika Dissawa; Nirmana Perera; Kapila Bandara; Prabath Binduhewa; Janaka Ekanayake (AIMS Energy, 2016)
With the recent cost reduction and efficiency improvement of solar photovoltaic (PV) cells, there is a growing interest towards PV systems in different applications. One promising application is solar PV powered electric vehicles. When they are moving on roads, the whole or some parts of the PV system might be shaded by trees, high buildings, etc.; which result in non-uniform insolation conditions. As a remedial measure, this paper presents a development of a cascaded multi-level inverter based PV system for electric vehicle applications. The basic architecture and switching of the converter switches are described. A laboratory prototype of the proposed architecture was implemented using MOSFETs and harmonic performance under different shading conditions was evaluated. It was found, that under shaded conditions, the 3rd harmonic content can increase and that it depends on the number of modules shaded and the loading condition. The shading performance, losses and power utilization of the cascaded multi-level inverter are compared with that of a conventional Pulse Width Modulated (PWM) inverter architecture. The proposed inverter shows better immunity for shading than a PWM inverter. Furthermore, it was found that the switching losses of the proposed inverter are one 10th to one 20th of that of a PWM inverter. Additionally, by properly selecting the switches, it is also possible to reduce the conduction losses compared to that of a PWM inverter. Even though the power utilization is compromised at full insolation, the power utilization performance of the proposed inverter is superior under shading conditions, thus ideally suited for the selected application. As the modular nature of the proposed inverter allows cascading of more H-bridges with fewer cells, the harmonic, shading, loss and power utilization performance of the proposed inverter can be enhanced with more number of steps in the output waveform.